ПРАКТИКО-ОРИЕНТИРОВАННЫЙ МОДУЛЬ РОБОТОТЕХНИКИ В ПРОФИЛЬНОЙ ПОДГОТОВКЕ УЧИТЕЛЕЙ ФИЗИКИ И ИНФОРМАТИКИ - Дудышева, Елена; Лопаткин, Николай (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article discusses the design and testing of a practice-oriented module on educational robotics in the vocational training of future teachers of physics and computer science at a pedagogical university. The module includes the development of the interdisciplinary content and conduct practical exercises with students. In the process of experimental work, it was shown that future teachers of physics and computer science can increase the level of special knowledge and skills in designing educational robots, if the form of training is an interdisciplinary module on educational robotics within disciplines "Electrodynamics" and "Computer architecture", and if one of the methods is working with schoolchildren on the assembly of robots under the supervision of university lecturers. The significance is the possibility of in-depth learning of junior courses students for future practical training using contemporary digital educational equipment. The practical tasks of the module contribute to the effective preparation of students if they are carried out in the process of working with students on educational robotic equipment, such as LEGO Mindstorms Education EV3 and Ultimate Robot Kit V2.0. The main issues of the educational robotics module–power supply of the robot, servomotors, sensors of robots, architecture of microcontrollers of robots–should be studied before completing tasks.